2013
DOI: 10.1111/eth.12173
|View full text |Cite
|
Sign up to set email alerts
|

Interpopulation Comparisons of Antipredator Defense Behavior of the Thorn‐Tailed Rayadito (Aphrastura spinicauda)

Abstract: The high impact of predators on breeding success has favored the evolution of diverse behavioral strategies that enhance both individual survivorship and reproductive success. Self‐ and nest‐defense against predators are inter‐related behaviors that vary according to life history traits and the risks involved in defense. In addition, interpopulation differences in the composition of predator guilds, and hence predation pressures, may result in geographic variation in antipredator defense strategies. It is gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…These studies suggest song sparrows show a greater mobbing response to a more threatening stimulus, similar to what has been found in studies of other bird species (Templeton et al 2005;Templeton and Greene 2007). Studies in several taxa have found that mobbing responses can be strong in animals even in populations where predators are absent (Ippi et al 2013;Owings and Coss 1977) and that animals can retain fear responses to absent or extinct predators Blumstein and Daniel 2002; Burns-Cusato et al -Jammes et al 2014). In addition, the correlation we observed between aggression and boldness (as measured by response to alarm calls) suggests that variation in response to alarm calls is strongly dependent on the personality of the responding individual-rather than the threat of predators in the habitat.…”
Section: Discussionsupporting
confidence: 69%
“…These studies suggest song sparrows show a greater mobbing response to a more threatening stimulus, similar to what has been found in studies of other bird species (Templeton et al 2005;Templeton and Greene 2007). Studies in several taxa have found that mobbing responses can be strong in animals even in populations where predators are absent (Ippi et al 2013;Owings and Coss 1977) and that animals can retain fear responses to absent or extinct predators Blumstein and Daniel 2002; Burns-Cusato et al -Jammes et al 2014). In addition, the correlation we observed between aggression and boldness (as measured by response to alarm calls) suggests that variation in response to alarm calls is strongly dependent on the personality of the responding individual-rather than the threat of predators in the habitat.…”
Section: Discussionsupporting
confidence: 69%
“…We tested each breeding pair three days after exploration experiments when nestlings were 15–16 d old. We placed a stuffed mount of a male rayadito at 3–5 m from the nestbox, and played back tape‐recorded songs of a male (see details in Ippi et al , ) during 10 min. A hidden observer at 10–15 from the nestbox recorded all behaviors on a Sony™ ICD‐BX700 ® digital voice recorder.…”
Section: Methodsmentioning
confidence: 99%
“…The same mount was used for all birds assayed and all experiments involved the same observer. Recordings were analysed with JWatcher to extract two variables: 1) alarm activity, measured as the total number of movements during the trial (Ippi et al ), and 2) the total number of aggressive interactions with the intruder, including pecking the intruder, flying over the intruder or hovering close to it. There was a moderate, positive correlation between the number of aggressive interactions and alarm activity (Pearson's r = 0.42, p = 0.08, n = 74).…”
Section: Methodsmentioning
confidence: 99%
“…During November 2013, as part of a long-term study of the breeding biology of the Thorn-tailed Rayadito (Aphrastura spinicauda) at Isla Navarino (55u 569 S, 67u 399 W; see Ippi et al 2013, Quirici et al 2014, located in the Magallanes and Chilean Antarctic Region, we observed two Chilean Swallows (Tachycineta meyeni) entering an occupied nest box and attacking a 13-day-old nestling rayadito. A pair of breeding rayaditos initially occupied the nest box on 6 October 2013, and five eggs were laid between 10-18 October.…”
mentioning
confidence: 99%
“…In both cases, only one swallow entered the box, while the other remained calling in flight nearby. Although breeding rayaditos are usually very aggressive towards any potential threat (see Ippi et al 2011Ippi et al , 2013, both adult rayaditos stayed away from the site during these interactions and emitted infrequent and faint alarm calls. This type of 'submission' behavior has never been reported in similar contexts, and its potential causes are difficult to explain.…”
mentioning
confidence: 99%